Exergoeconomic analysis of a steam turbine power plant in a sulfuric acid factory - Maged Galal; Rafea Abd El Maksoud; N.N. Bayomi (Results in Engineering)
This study presents an exergoeconomic analysis of a steam turbine power plant (STPP) implemented within a sulfuric acid production facility. The plant harnesses waste heat from an exothermic chemical reaction to generate electricity. A detailed mathematical model was developed in Engineering Equation Solver (EES) to perform the exergoeconomic assessment on individual components and the overall system.The STPP generates 4.7 MW of electricity, with an exergoeconomic factor of 33 %. The exergy cost and unit exergy cost of the electricity are 455.8 $/h and 26.94 $/GW, respectively. The turbine represents the highest capital cost within the system. The steam produced incurs an exergy cost of 640.7 $/h, with a unit exergy cost of 2.2 $/GW. The waste heat boiler exhibits the highest exergy destruction cost at 112 $/h, and the major exergy destruction cost ratios are observed for the waste heat boiler (0.23 W/$) and the turbine (0.51 W/$). Additionally, the impact of variations in steam inlet temperature and pressure on the exergoeconomic performance was analyzed.These findings provide valuable, cost-based indicators such as exergy destruction cost, exergoeconomic factor, and exergy destruction cost ratio, which can guide the optimization and practical implementation of STPPs in the sulfuric acid industry.